Upravna akademija - potreba in izziv - Purg, Adam (Teorija in praksa, 1996)
The author presents key conclusions of the Administration Academy project, going on within the Swiss - Slovene project of modernising public administration in Slovenia (MASTER PROJECT). By different methodological approaches, the participants of the MASTER PROJECT have accomplished, through research, the most ever done of the present situation and the future training needs within the Slovene administration. Combining comparable foreign experiences and domestic ideas and resources, this research could be a basis for the introduction of effective solutions. One of them is the establishment of Administration Academy that could carry out the entire training system for senior and other public servants at all levels and thus contribute to the modernisation of public administration in Slovenia.
Keywords: uprava; javna uprava; modernizacija; upravna akademija; Master projekt; usposabljanje